Web-Based Applications in Healthcare and Biomedicine - Lazakidou, Athina; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This proposed Special Issue in AoIS will present studies from leading researchers and practitioners focusing on current challenges, directions, trends, and opportunities associated with healthcare organizations and their strategic use of Web-enabled technologies. Healthcare and biomedical organizations are undergoing major transformations to meet the demand for improved access and quality of service, and modern information technologies are helping to process and manage the growing wealth of data involved. Web-based applications offer a sharp increase in data access and management, and they are at the forefront of the broad field of medical informatics. Topics to be covered will include semantic web applications; workflow and process management; content management and portal technology; data and web mining, warehousing, and information collection, curation, and analysis; web-based learning environments; access control and security; transaction management; and tools for implementation.
Development and Evaluation of a Web-Based Personal Electronic Health Record (pEHR) -- Exploring the Potential of Over-the-Web Psychiatry -- An Intelligent Web-Based Healthcare System: The Case of DYMOS -- An Empirical Study of Sections in Classifying Disease Outbreak Reports -- A Web-Based Application to Exchange Ophthalmologic Health Records Using Open-Source Databases -- An Image-Centric, Web-Based, Telehealth Information System for Multidisciplinary Clinical Collaboration -- SOAP/WAD-Based Web Services for Biomedicine -- Web Resources for Gene List Analysis in Biomedicine -- Web-Based Applications in Healthcare -- Evaluation for Web-Based Applications -- Web-Based Communities for Lifelong Medical Learning -- Evaluation of Wikis Exploited for Medicine Courses Teaching -- Computer-Based Oxygen Transport Scenario Analysis: A New Web-Based Medical Education Resource -- Development of an Educational Web Site to Assist in Learning Clinical Airway Management -- An Integrated Approach in Medical Decision-Making for Eliciting Knowledge -- Using Decision Trees for the Semi-automatic Development of Medical Data Patterns: A Computer-Supported Framework -- Telemedicine for the Diabetic Foot: A Model for Improving Medical Care, Developing Decision Support Systems, and Reducing Medical Cost -- SOAP/WAD-Based Web Services for Biomedicine.
Keywords: Life sciences; Medical records -- Data processing; Bioinformatics; Life Sciences; Bioinformatics; Health Informatics